Visual Identity and Promotion Media for Integrated Tourism of North Jakarta - Ratna Sari; Didit Widiatmoko Soewardikoen (KK Komunikasi Visual & Multimedia Fakultas Seni Rupa dan Desain Institut Teknologi Bandung, 2014)
North Jakarta is coastal areas of DKI Jakarta city which has much more opportunity in improving the interesting potential tourism, not only for citizen in Jakarta but also for Indonesian. However, location of various tours which is scattered throughout North Jakarta and the lack of strong visual identity and promotion media for tourism of North Jakarta that can be accessed easily, make a lot of people didn't know about North Jakarta.Data collecting is carried out through observation, interviews, and related literature. Place symbolization approach are used in designing to achieve the visual identity and promotion media that can unite all of tour destinations of North Jakarta. The result from this research is the designing identity visual of North Jakarta Tourist Destinations using symbol and tagline that are readable and memorized easily by target audiences.Visual identity that includes North Jakarta's Tourism logo, icons of North Jakarta's destinations, and also on promotion media will be used in various media such as map, poster, website, x-banner, guide book, ticket, signage, merchandise and social media so they can help tourism of North Jakarta to be more easily recognized by tourist and can attract the tourist to visit the variety of tour destinations at Jakarta Utara.